KEPERCAYAAN DAN FASILITAS DALAM MEMBENTUK LOYALITAS PELANGGAN DI HOTEL GRASIA SEMARANG - Prabowo, Heri (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2021)
The establishment of new hotels in Semarang City has an impact on increasing competition between existing hotels. Many hotel choices make the hotel room occupancy rate reduced. Based on the increasing number of existing hotels that have an impact on decreasing occupancy rates, research on customer loyalty is conducted. The research was conducted at Grasia Hotel with 96 respondents with criteria as guests who have stayed more than twice and for criteria aged more than 20 years. The results showed that trust and facilities had a positive effect on customer loyalty